Poly(propyleneimine) glycodendrimers non-covalently bind ATP in a pH- and salt-dependent manner – model studies for adenosine analogue drug delivery - Gorzkiewicz, Michal; Buczkowski, Adam; Appelhans, Dietmar; Voit, Brigitte; Pulaski, Lukasz; Palecz, Bartlomiej; Klajnert-Maculewicz, Barbara (International Journal of Pharmaceutics, 2018)
Adenosine analogue drugs (such as fludarabine or cladribine) require transporter-mediated uptake into cells and subsequent phosphorylation for anticancer activity. Therefore, application of nanocarrier systems for direct delivery of active triphosphate forms has been proposed. Here, we applied isothermal titration calorimetry and zeta potential titration to determine the stoichiometry and thermodynamic parameters of interactions between 4th generation poly(propyleneimine) dendrimers (unmodified or sugar-modified for increased biocompatibility) and ATP as a model adenosine nucleotide. We showed that glycodendrimers have the ability to efficiently interact with nucleoside triphosphates and to form stable complexes via electrostatic interactions between the ionized phosphate and amino groups on the nucleotide and the dendrimer, respectively. The complexation process is spontaneous, enthalpy-driven and depends on buffer composition (strongest interactions in organic buffer) and pH (more binding sites in acidic pH). These properties allow us to consider maltose-modified dendrimers as especially promising carriers for adenosine analogues.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Adenosine-5′-triphosphate (ATP); Complexation; Glycodendrimers; Nucleoside analogues (NAs); Poly(propyleneimine) (PPI) dendrimers